Information spread behavior of clubhouse: A value-attitude-behavior model perspective - Yu-Feng Wu; Yu-Tai Wu; Jian-Hong Ye; Jhen-Ni Ye (Heliyon)
The prevalence of social media has significantly facilitated the spread and diffusion of online memes. The Clubhouse voice community application, which gained popularity rapidly during the COVID-19 pandemic and became widely used, can be regarded as a form of internet meme. However, the underlying reasons for this phenomenon have been scarcely explored. In this context, the purpose of this study is to understand the dissemination mechanisms of the Clubhouse voice community. Specifically, this research employs the value-attitude-behavior model to investigate the relationships between social value, attitude, immediate response syndrome, and information spread behavior on Clubhouse. To achieve this objective, the snowball sampling technique was used to recruit Clubhouse users to complete a questionnaire. The collected data were assessed for reliability and validity before being analyzed using structural equation modeling for confirmatory factor analysis and model verification. The results indicated that the social value of joining Clubhouse is positively associated with participants’ attitudes toward participation. Additionally, attitudes toward participation were found to be positively associated with both immediate response syndrome and information spread behavior, thus showing a positive association between immediate response syndrome and information spread behavior. This study reveals the pathways of internet meme dissemination, offering insights into the factors driving the formation of internet memes.